Esteroides anabólicos androgênicos e seus efeitos associados ao treinamento de força de ratas wistar eutróficas - Santos, Wiliane Nery (2017)
Introduction: Strength training has been consistently demonstrated in studies as responsible for significant increases in lean mass and metabolic rate, accompanied by significant reductions in body fat weight, using strategies to accelerate this process androgenic anabolic steroids has been enough used by practitioners of this modality. Objective: To evaluate the strength training acting in conjunction with Androgenic Anabolic Steroids on the percentage of body fat of eutrophic rats. Methods: Twentyfour female rats randomly distributed in four groups were used: 1) Sedentary Control (CS) 2) Trained Control (CT) 3) Sedentary Nandrolone Decanoate (DS) 4) Trained Nandrolone Decanoate (DT). Strength training was performed in a squatting apparatus composed of four sets of 12 repetitions, with intensity of 70% of 1RM for eight weeks. On alternate days, the DS and DT groups received daily 5 mg/kg nandrolone decanoate intraperitoneally and the CS and CT groups received only saline solution (0.9%). The data represent the mean ± standard error of the mean. Student's t-test was used for analysis between groups, ns = no statistical difference. Results: After eight weeks of training, the weight between the CS and CT groups were different when compared to the DS and DT groups (there was no statistical difference between groups (CS vs CT, DS vs DT), in this sense, the CT group Who underwent strength training had a 10.8% and 11.2% increase in strength, in the 6th and 8th weeks, respectively, when compared to the CS group. The fatty contents of different territories were evaluated as follows: subcutaneous (SUB), retroperitoneal (RETRO) and periovarian (PERI) fats, which did not identify statistical differences between the groups evaluated. Conclusion: The use of Nandrolone Decanoate in trained rats did not cause changes in weight, strength and adipose tissue.